Fluorescent organometallic rhodium(I) and ruthenium(II) metallodrugs with 4-ethylthio-1,8-naphthalimide ligands: antiproliferative effects, cellular uptake and DNA-interaction - Streciwilk, Wojciech; Terenzi, Alessio; Cheng, Xinlai; Hager, Laura; Dabiri, Yasamin; Prochnow, Pascal; Bandow, Julia Elisabeth; Wölfl, Stefan; Keppler, Bernhard K.; Ott, Ingo (European journal of medicinal chemistry, 2018)
Fluorescent 4-ethylthio-1,8-naphthalimides containing rhodium(I) N-heterocyclic carbene (NHC) and ruthenium (II) NHC fragments were synthesised and evaluated for their antiproliferative effects, cellular uptake and DNA-binding activity. Both types of organometallics triggered ligand dependent efficient cytotoxic effects against tumor cells with the rhodium(I) NHC derivatives causing stronger effects than the ruthenium (II) NHC analogues. Antiproliferative effects could also be observed against several pathogenic Gram-positive bacterial strains, whereas the growth of Gram-negative bacteria was not substantially affected. Cellular uptake was confirmed by atomic absorption spectroscopy as well as by fluorescence microscopy indicating a general ligand dependent accumulation in the cells. An in-depth study on the interaction with DNA confirmed insertion of the naphthalimide moiety between the planar bases of B-DNA via an intercalation mechanism, as well as its stacking on top of the quartets of G-quadruplex structures. Furthermore, additional coordinative binding of the organometallic complexes to the model DNA base 9-ethylguanine could be detected. The studied compounds thus represent promising bioorganometallics featuring strong pharmacological effects in combination with excellent cellular imaging properties.
Gesehen am 20.04.2020